Wind-powered water pumping system for corn plantations under the food estate program on Sumba Island, Indonesia - Aziz, Amiral; Rostyono, Didik; Zaky, Toha; Hesty, Nurry Widya; Ifanda, Ifanda; Fauziah, Khotimatul; Prasetyo, Ridwan Budi; Wijayanto, Rudi Purwo; Witjakso, Ario; Syawitri, Taurista Perdana; Mayasari, Agustina Putri (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The Food and Agriculture Organization (FAO) released a communiqué in March 2020 cautioning about the possibility of a worldwide food emergency due to coronavirus disease (COVID-19). As a response to the food shortages brought on by the COVID-19 outbreak, the authorities of Indonesia initiated a nationwide program aimed at improving the country's food supply known as the food estate (FE), which was later incorporated into national strategic programs. The climate and availability of surface water sources in this region make establishing an FE area in the Central Sumba Regency difficult. Sumba, on the other hand, possesses wind energy resources that can be transformed into electrical energy and used to pump underground water for agricultural purposes. A wind-powered water pump (WPW) is being developed in this study to provide water for maize plantations in the FE region in Central Sumba District, Indonesia. The study on the levelized cost of energy (LCOE) for water pumping indicates that the wind-powered system is more economically viable than the diesel-powered alternative. The LCOE for a WPW pumping system is 6,994 IDR/kWh, whereas the LCOE for a diesel-powered system is 16,667 IDR/kWh. The overall net present value of WPW and diesel-powered systems is 708,667,200 IDR and 2,158,349,000 IDR, respectively. This study contributes significantly to informed decision-making for enhancing the performance viability of the wind water pumping system for the food estate program in Indonesia.